Design of room capacity measurement and body temperature detection based on atmega328 microcontroller. Issue 1 (1st February 2022) - Azhari; Marbun, Hertika; Karolina, Rahmi; Hakim, Lukman
Abstract: The outbreak of Corona Virus Disease 2019 (Covid 19) cases that occurred from 2020 until now limits the current maximum allowed room capacity, which is only around 25% to 50% of the maximum room capacity. The purpose of this study is to design a device that can detect temperature and limit room capacity automatically as an effort to prevent the transmission of the covid 19 virus. In designing a room capacity measuring device and an atmega328 microcontroller-based body temperature detector with a viewer on an android smartphone. The ultrasonic sensor HC-SR04 is used to measure the capacity of the room to determine the number of people entering and leaving. Then this tool also uses the MLX90614 sensor to detect the body temperature of everyone who wants to enter with the temperature conditions below 38°C. When both sensors have worked according to their functions, the doorstop can be opened. The results of the data obtained on each sensor will be sent to the microcontroller as a control center on a system so that it can be displayed on the LCD and using an additional device, namely esp8266 as a wifi communication module. After testing it can be concluded that the tool works well. The comparison of the results of the MLX90614 sensor with a standard tool. The data obtained is quite accurate with maximum error only 2.2% with the comparison tool.